Receiving COVID-19 Messages on Social Media to the People of Semarang City - Desty, Rani Tiara; Arumsari, Wahyuni (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
During the COVID-19 pandemic, social media has become one of the ways to convey information quickly with internet technology. Of the many uses of social media in obtaining information about COVID-19. Of course, not all are accurate. There are many hoaxes or fake news, while on the other hand, the news happened according to the facts. Confirmed cases found in Semarang City were 88,014 cases with a death toll of 4,460 people. This study aims to find out how to receive information about COVID-19 on social media in the community of Semarang City. This study uses an analytic observational study with a cross-sectional design conducted in June-July 2021. The research sample is Semarang residents who have social media with an age range of 15-65 years. The results showed that 68% of respondents believed in information related to COVID-19 on social media. 80% can distinguish hoaxes from true information related to COVID-19 from social media. 71% of respondents confirmed the truth of the news obtained about COVID-19 from Social media. Some respondents believe in the information on social media WhatsApp, Instagram, Facebook, Youtube, Twitter, and Telegram. So growing digital literacy skills are expected to help the government overcome the issue of corona hoaxes and vaccines that are still emerging. The improved critical way of thinking is expected to be the countermeasure.